Critical level of available sulphur in the soil during establishment of clones of yerba mate at Southern Brazil - Schmitt, Djalma Eugênio; Vendrusculo, Rodrigo Balen; Gatiboni, Luciano Colpo; Santin, Delmar; Wendling, Ivar; Dall’Orsoletta, Daniel João; Coldebella, Flávia Denise (Revista de Ciências Agroveterinárias, 2018)
The cultivation of yerba mate (Ilex paraguariensis St. Hil.) has great economic importance in the Southern of Brazil. However, the fertilization requirements in the establishment of yerba mate plantations is still unknown. The objective of this work was to evaluate the needs of sulfate fertilization on the initial growth of two clones of yerba mate in a Humic Cambisol. An experiment was carried out in Itaiópolis - SC and four doses of S (0.0; 1.2; 2.4 and 3.6 kg ha-1 of S-SO42-) and two clones (F1 and F2) were tested. The green mass and the export of nutrients were evaluated: leafs, fine twigs, thick twigs and commercial yerba mate (leaf + fine twigs), and total mass. Soil available S-SO4 was evaluated in the 0-20 cm soil layer 24 months after planting. The production of thick twigs increased with application of S, for clone F2. However, the yield of fine twig and total mass were influenced by the dose of S, independent of the clone. Thus, there was a positive response from the application of sulfur to clone F2, indicating that it is demanding on the nutrient, increasing the yield of green mass and the levels of S-SO4 in the soil.